Success in Research: Factors that Contribute to Increased Research Productivity Across Librarianship and Other Disciplines - Hoffmann, Kristin; Berg, Selinda; Koufogiannakis, Denise (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2016)
Research is a professional responsibility for many academic librarians. Some are successful researchers; others struggle to be productive. This content analysis is part of a larger study designed to develop an instrument to determine the factors contributing to librarians' success in research. This presentation highlights similarities and differences in success factors discussed in LIS and other disciplinary publications. La recherche est une responsabilité professionnelle pour de nombreux bibliothécaires universitaires. Certains sont de bons chercheurs; d'autres luttent pour être productifs. Cette analyse de contenu fait partie d'une étude plus large visant à élaborer un instrument permettant de déterminer les facteurs qui contribuent à la réussite des bibliothécaires dans la recherche. Cette présentation met en lumière les similarités et les différences dans les facteurs de réussite tels qu’ils sont discutés dans les publications spécialisées en sciences de l’information et bibliothéconomie et dans d’autres publications disciplinaires.